Characterizing historic land use and land cover change using landsat earth obsrvation data in the Waterberg biosphere reserve - Mundalamo, Tsedzuluso Dylan (My University, 2019)
Information about Land use and land cover (LULC) is important for making a better decision, planning, and management of human activities and natural resources in protected, conserved and unprotected areas such as river catchment area and biosphere reserve. The study was conducted in the Waterberg region to characterize and compare historical landscape modification within the Waterberg Biosphere Reserve (WBR) and the surrounding river catchments, both prior to and after its promulgation with United Nation Education Scientific and Cultural Organization’s Man and Biosphere Programme in 2001. The research objectives of this study were to map the LULC classes from 1984 to 2016 in successive five years interval using the Landsat 4-5, 7 and 8 images, quantify LULC changes within and outside the WBR (River catchment areas) and lastly, quantify the impact of the WBR on urban and agriculture. Information about LULC was derived using Support Vector Machine (SVM) algorithm with 140 reference data for each LULC class (70% as training data and the remaining 30% as validation data). The Normalized Difference Vegetation Index (NDVI) and statistical testing (paired t-test) were computed and performed, respectively. The overall accuracies range from 80.29% to 90.12%, User’s accuracies (50.65 to 100%), producer’s accuracies (45.24% to 100% and kappa indices (0.78 to 0.81) Landscape has insignificantly modified over the analysis period (P >0.05) on both sides of the study whilst the NDVI shows significant change (P<0.05). Cultivated land decreased on both sides of the WBR as land covered by this LULC type was 8.41% (Inside) and 7.52% (Outside) in 1984 and decreased to 4.04% and 4.90% inside and outside the WBR respectively, in 2016. Built up area increased outside the WBR as it was 1.04% in 1984 and 1.59% in 2016. However, built up area decreased from 0.79% in 1984 to 0.69% in 2016 outside the WBR. Mines occur outside the periphery of the WBR and increased from 0.04 %( 1984) to 0.13% (2016). Waterbody also increased from 0.10% inside and 0.01% outside the WBR in 1984 to 0.13% and 0.04% respectively, in 2016. The area is experienced rapid urban and mine growth which raise concern on the quality of water, aquatic species and ecosystem functionality as the WBR did not halt these developments within the region as it holds the potential coalfields to supply coal for fossil energy generation. The conversion of cropland to game farming caused revegetation which could influence the ecological functioning of both aquatic and terrestrial ecosystems. Proper planning and management of both human activities and natural resources are recommended to conserve the biodiversity while promoting local community involvement in sustainable development structures.
A research report submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in partial fulfillment of the requirements for the degree of Master of Science (Geographical Information Systems and Remote Sensing) at the School of Geography, Archaeology & Environmental Studies Johannesburg 2019